Pembangkitan Fraktal Koch Anti-Snowflake (m,n,c) Menggunakan Metode Transformasi Affine - Alkhori, Ellenda Alkhori; Purnomo, Kosala Dwidja; Juliyanto, Bagus (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami); Vol 3 No 1 (2019): Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai Islami), 2020)
Fractal Koch Anti-Snowflake (m,n,c) is a developmental form of fractal Koch Anti-Snowflake (m,n,c) with variation of m is initiator (basic form) using polygon- m and with variation of n is generator (iteration) using polygon- n . While c the size of the middle segment that removed on each side of initiator. Each iteration on generation procedure of Koch Anti-Snowflake (m,n,c) using affine transformation method will produce several forms, the first form is Koch Anti-Snowflake (m.n,c) that does not intersect with variation of initiator polygon-m , variation of generator polygon- n , and the selected c value that is a half the upper limit value ​​have been specified. The Second forms is Koch Anti-Snowflake (m,n,c) coincide with a variation of the initiator polygon- m , variation of generator polygon- n and there are variation value of  c which is less than half of the upper limit in the value of c selected. The third form is Koch Anti-Snowflake (m,n,c) intersect with a variation of the initiator polygon- m and variation of generator polygon- n , variation of the initiator polygon- m and variation of generator polygon- n with the selected variation c value which is close enough with the  upper limit of  value specified is c-0,00001.